Prospects for land-use sustainability on the agricultural frontier of the Brazilian Amazon - Galford, Gillian L. (The Royal Society, 2013)
The Brazilian Amazon frontier shows how remarkable leadership can work towards increased agricultural productivity and environmental sustainability without new greenhouse gas emissions. This is due to initiatives among various stakeholders, including national and state government and agents, farmers, consumers, funding agencies and non-governmental organizations. Change has come both from bottom-up and top-down actions of these stakeholders, providing leadership, financing and monitoring to foster environmental sustainability and agricultural growth. Goals to reduce greenhouse gas emissions from land-cover and land-use change in Brazil are being achieved through a multi-tiered approach that includes policies to reduce deforestation and initiatives for forest restoration, as well as increased and diversified agricultural production, intensified ranching and innovations in agricultural management. Here, we address opportunities for the Brazilian Amazon in working towards low-carbon rural development and environmentally sustainable landscapes.